Management of Electric Field under the Sag of High Voltage Overhead Transmission Lines - Mester Sitepu; Martha Rianna (Talenta Publisher, 2020)
There have been many methods used to determine the electric field strength under the 150 KV overhead transmission lines (OHTL). Since it is simple and can be used for a homogeneous and multilayer medium, the method chosen for modeling the electric field under the OHTL is the complex image method (CIM). The results obtained show that the electric field strength obtained by the CIM is in agreement with that obtained by Complex Determine Method (CDM). Furthermore, the results obtained from the CIM model fit well with the field data. The OHTL height that must be raised so that the electric field strength under the OHTL will meet the WHO quality standards is 3 m at location A and 2 m at location B. These results show that modelling the electric field under the OHTL using CIM is exellent.